The Constitution Besieged The Rise & Demise of Lochner Era Police Powers Jurisprudence - Gillman, Howard (Book collections on Project MUSE., 1993)
The Constitution Besieged offers a compelling reinterpretation of one of the most notorious periods in American constitutional history. In the decades following the Civil War, federal and state judges struck down as unconstitutional a great deal of innovative social and economic legislation. Scholars have traditionally viewed this as the work of a conservative judiciary more interested in promoting laissez-faire economics than in interpreting the Constitution. Howard Gillman challenges this scholarly orthodoxy by showing how these judges were in fact observing a long-standing constitutional prohibition against "class legislation." By reviewing unfamiliar state cases and legal commentary, and by providing fresh interpretations of familiar Supreme Court cases, Gillman uncovers a fascinating - and long forgotten - legal tradition. In this richly textured historical narrative, we see how American judges once worked to insure that legislative power be used only to promote the public good, and not to benefit certain classes or burden their market competitors. Beyond shedding new light on this jurisprudence, Gillman also links it to larger debates in the political system, debates traced to concerns about factional politics expressed by the country's founders and to the Jacksonian assault on special privileges. This tradition came under siege with the intensification of class conflict at the turn of the century, and Gillman carefully documents its demise. He details how industrialization undermined assumptions about the fairness of capitalist social relations, and how this led increasing numbers of people to question the requirement that the state remain neutral in matters of class conflict - thus leaving it to a stalwart judiciary to protect "a Constitution besieged." A major contribution to an understanding of this important period in the history of the Supreme Court, Gillman's work stands as a landmark in revisionist accounts of the "Lochner era." Gillman's study represents the kind of paradigm-shift that will undoubtedly affect a wide range of scholarly activity for some time to come. The broad scope of this work makes it essential reading for those interested in American political thought, the development of the American state, the relationship between law and social change, and contemporary debates about the original intent of the framers of the Constitution and the proper role of the judiciary in American politics.